2004
DOI: 10.1097/01.sle.0000148462.46899.61
|View full text |Cite
|
Sign up to set email alerts
|

Early and Mid-term Results of Totally Laparoscopic Surgery for Aortoiliac Disease

Abstract: The present article is the first in the literature reporting short- and medium-term results using a totally laparoscopic technique for aortoiliac disease.Forty-nine patients, 6 having an associated small aneurysm, were scheduled for totally laparoscopic surgery (TLS) for aortoiliac occlusive disease and 2 for treatment of aortic aneurysmal disease (AAA). Patients' characteristics, intraoperative, postoperative data and mid-term data were recorded.TLS was successfully completed in 45 patients. Of those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 21 publications
1
27
1
2
Order By: Relevance
“…Previous series have already demonstrated that these well-known advantages of laparoscopy were also valid after laparoscopic aortic surgery. 8,9,21,[24][25][26][27][28][29][30] We did not observe adverse events after a median follow-up of 19 months. These data are similar to those of open repair and demonstrate the mid-term reliability of laparoscopic JAAA repair.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous series have already demonstrated that these well-known advantages of laparoscopy were also valid after laparoscopic aortic surgery. 8,9,21,[24][25][26][27][28][29][30] We did not observe adverse events after a median follow-up of 19 months. These data are similar to those of open repair and demonstrate the mid-term reliability of laparoscopic JAAA repair.…”
Section: Discussioncontrasting
confidence: 48%
“…When stents and surgical bypass are compared the cumulative 18 months patency has favored surgical bypass (93 vs. 77%) [11]. Dion and others have reported a conversion rate from totally laparoscopic procedures to hand-assisted or mini-laparotomy procedures of 10-15% which is consistent with our conversion rate of 16% [7,12].…”
Section: Discussionsupporting
confidence: 90%
“…Stadler et al were able to perform the aortic anastomosis with robotic assistance in a mean clamp time of 54 versus 99 min when done totally laparoscopically by Dion [3,7]. Our own clamp time was a median of 75 min while our animal model laparoscopic aortic anastomosis time was in excess of 100 min.…”
Section: Discussionmentioning
confidence: 89%
“…Compared to various larger series [4,7,9,12,14,15], the aortic anastomosis time and the aortic clamp time in this series became acceptable after the first 8 patients. In our institution patients are treated by endovascular techniques for aortoiliac occlusive disease, and only a few patients need surgery.…”
Section: Discussionmentioning
confidence: 86%